Assessment of Official Bond as an Intangible Asset and Its Implications on the Restitution of State Losses Due to Violations Against the Official Bond at the Ministry of Finance - Mumpuni, Mila; Martin, Ade Sonny (Jurnal Dinamika Akuntansi, 2016)
Official Bond is a common form of engagements in an education institution funded by an agency. The engagements result that the granted parties must work for a certain period. The violation against this official bond will cause disadvantages for the agency that has funded the educational process that is subject to claims for compensation against the offending party. One of the government agencies that implement the official bond is the Ministry of Finance. Based on the data from 2010-2014, the state losses due to the violations against the Official Bond in the Ministry of Finance showed less optimal performance. One of important obstacles in the completion of the bond violations is the difficulty in determining the value of the state losses. This paper aims to develop the possibilities of the Official Bond recorded as an Intangible Asset and its implications toward the restitution of the state losses due to the violations against the official bond at the Ministry of Finance.